Suplementação mineral de novilhas leiteiras em pasto de capim-marandu - Alcoforado, Carlos Augusto de Almeida Targino (2017)
This study aim was evaluate the performance of dairy heifers in growing under two mineral supplementation strategies. Was used 16 Holstein x Zebu heifers with 135.25±15,50 kg average weight, divided into 2 treatments (protein salt and mineral salt) and managed in Brachiaria brizantha pasture Marandu cultivar under rotational system with 28 paddocks (14 per treatment) with 2 occupation days and 26 rest days for 6 consecutive cycles, being cycles 1, 2 and 3 related to Spring season and the cycles 4, 5 and 6 to Summer season. At the end of each 28-day cycle, the animals were weighed and the ADG weight used for calculation and allocation rate. The pasture height and herbage mass were measured before entering and after leaving the animals in each paddock, where samples were taken for chemical analysis and consumption estimates (MS, CP, EE, NDF, iNDF and DMpd), plus of DM digestibility estimates, pre-grazing herbage mass, herbage mass post-grazing, consumption and forage supply, composition (leaf, stem and senescent material). The supplements were provided ad libitum in suitable troughs and the end of each cycle were measured the supplement consumption. The design was completely randomized with portion sub-divided in time, where the two treatments were the supplements, the stations were the plots and animals as repetitions. There was no difference (P> 0.05) between treatments, stations and interaction treatment x station to the ADG were 301.12 and 357.13 g day-1 for animals supplemented with mineral salt and protein salt. A significant effect (P <0.05) between the evaluated seasons (Spring / Summer). We observed a significant effect (P <0.05) between the evaluated seasons (Spring / Summer). The average dry matter intake (kg day-1,% BW and g / kg0.75), crude protein (g day-1 g / kg0.75), ether extract (g day-1), neutral detergent fiber (g day-1 and BW%) were respectively 3.94 and 2.87 kg; 2.53 and 1.69%; 89.26 and 59.56 g kg0.75; 429.89 and 238.42 g day-1; 9,74 and 6,17g kg0.75; 118.79 and 84.07 g day-1; 2.98 and 2.05 kg day-1; 1.86 and 1.17%, for the Spring and Summer seasons. The supplement intake was different (P <0.05) between the treatments were 36.50 and 65.50 g 100 kg-1BW. The DM digestibility was significant (P <0.05) to interaction, treatment x station whose values were 49.76 and 46.80 for animals supplemented with mineral salt and protein salt respectively in the Spring and 47,00 and 50,39 for these same treatments in Summer.